Analyzing Content An ESP Textbook: English International Tourism By Peter Strutt - Abdul Syahid; Siti Rahimah; Fajariah Fajariah; Rini Listiya Ningrum; Krisna Dwi Alifhia Rezky (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
This research aimed to analyze the content of the English textbook "English for International Tourism" by Peter Strutt using the approach proposed by Brian Tomlinson. The research utilized a qualitative descriptive technique through checklist observations of several indicators of book content criteria. The analysis focused on the relevance, coherence, learner engagement, suitability, readability, and creativity of the materials presented in both textbooks. The findings revealed that "English for International Tourism" successfully presented updated, varied, engaging, and challenging content that not only fostered learner engagement in the tourism industry but also aided in developing learners' confidence and relevant language skills. Moreover, this book met various criteria for effective language learning materials, including facilitating learner comfort, building confidence, providing relevant and useful content, and offering opportunities for communicative language use. The book also considered various learning styles, affective attitudes, and provided feedback for delayed positive instructional effects.